Dugout. The zombie steals home - Morse, Scott (Graphix, 2019)
Twins Stacy and Gina Cavallaro, the youngest in a long line of family witches, find themselves on opposite sides of rival little league teams. Stacy, the true athlete, dominates the league with her pitching while Gina and her eclectic team of misfits hasn't won a game all season. In the heat of the moment, Gina casts a spell on Stacy, which backfires spectacularly when she accidentally raises a zombie. Stacy then accidentally curses Gina which summons a ghost. The two must reluctantly put aside their differences to manage the two unwanted monsters together.